A Study On Computer Programmes Applied For Solar Simulation In Architecture And Urban Design - Mazloomi, Mehrdad; Hassan, Ahmad Sanusi (2008)

(untitled)
This paper conducts a study on the computer programmes which are applied to simulate solar radiation in research area of urban development and architecture.